Church history and elite formation the experience of Manaoag - Amador, Kim Mikael G.; Sagaionit, Glenn V. (2001)
The study is a qualitative inquiry concerning the emergence of entrepreneurial elites in the town of Manaoag, Pangasinan. The elites referred herein are those elites who emerged as a result of the influx of pilgrims and created a shift in the socio-economic attributes of the town. Through the study, the researches have identified the indicators of the town's growth such as livelihood patterns, number of religious devotees and infrastructure development as well as the contribution of entrepreneurial elites on these aspects. It was found out in the study that the most visible contribution of elite formation is in the livelihood patterns of Poblacion, Manaoag, Pangasinan --Author's abstract.